THE IMPACT OF VILLAGE EXPANSION ON SOCIO-ECONOMIC DEVELOPMENT IN HUTAKALO VILLAGE SUMALATA DISTRICT IN (2009-2020) - Pitoi, Lisna; Manay, Helman; Malae, Andris K. (CV. Fahr Publishing, 2025)
This study aims to determine and describe the impact of the expansion and socio-economic development of Hutakalo Village in the period 2009 to 2020. The issues raised include how the process of expansion of Hutakalo Village in 2009-2010 and how the impact of socio-economic development after the expansion of the village in 2009-2020. The research method used is the historical research method, which includes the stages of heuristics, source criticism, interpretation, and historiography. Heuristics is carried out by collecting data through primary and secondary sources. Source criticism is applied through analysis of written and unwritten sources. The interpretation stage involves combining and analyzing data obtained from primary and secondary sources, and the results of the researcher's observations. The final stage, historiography, is the compilation of research results based on the stages of heuristics, source criticism, and interpretation. The results of this study indicate that the ratification of Hutakalo Village through the Regional Regulation of North Gorontalo Regency Number 66 of 2010, which was then inaugurated in 2011. After the expansion, Hutakalo Village experienced development in various sectors. In the social aspect, namely the Level of Education and the Level of Population Growth that is consistent every year, while in the economic aspect, namely the increase in the number of Micro, Small, and Medium Enterprises (MSMEs) shows an improvement in the socio-economic conditions of the community after the expansion and the level of development in Hutakalo Village.